Five trends in government liability under environmental laws: implications for public administration - O'Leary Rosemary
What are the implications of our changing environmental laws for U.S. public administration? In this article, Rosemary O'Leary examines five trends in government liability under environemntal laws: (1) the erosion of government immunity; (2) criminal liability of lower and middle level government employees; (3) increased reporting requirements; (4) the municipality as water pollution control agency; and (5) liability for regulatory takings. O'Leary concludes that these developments will prompt nothing less than a fundamental change in public administration as we know it today. Proactive steps, such as using the budgetary process as a defensive mechanism, are suggested as a means of addressing the challenges t
Keywords: Pollution -- U.S.A.; Public Administration -- U.S.A.; Environmental Policy -- U.S.A.